INVESTIGATION OF THE THIN LAYER DRYING OF MICROPROPAGATED OCIMUM BASILICUML: MODELING BY DERIVED EQUATIONS, QUALITY CHARACTERISTICS, AND ENERGY EFFICIENCY - Kalender, Mehmet; Topdemir, Aykut (Assoc Chemical Eng, 2023)
This study presents the modeling of thin layer drying of micropropagated Ocimum basilicum L., some quality characteristics of the dried product, and energy consumption analysis for the dryer used. The experimental drying data obtained from a previous article were used in the statistical analyses. Modeling studies were statistically carried out using the experimental data at a 1 m/s airflow rate and a temperature of 30 degrees C-50 degrees C. The statistical analysis showed that the Verma equation was the best-fit model with the lowest chi-square (chi 2) and AIC values at all temperatures studied. From statistical analyses using derived drying models, it was found that the D9 equation having a chi 2 value of 0.0146 and an AIC value of-528.0, was the best model fitting to experimental data. The total phenolic content, flavonoid, and antioxidant capacity of dried basil samples were measured as (2.538 +/- 0.029) mg GAE/g, (2.017 +/- 0.088) mg quercetin/g, and (2.263 +/- 0.001) mmol TEAC/100 g d.w., respectively. From FTIR spectra, dried basil samples had typical functional groups. SEM images showed that a collapse in the surface of the leaves occurred. But, this collapse is not affecting the functional groups on the surface of the leaves. From energy consumption analyses, the optimum drying temperature was found to be 40 degrees C. The SMER, MER, and SEC values calculated from energy consumption analysis at 40 degrees C were 0.0043 kg/kWh, 0.0007 kg/h, and 234.81 kWh/kg, respectively.
ISTRA?IVANJE SUŠENJA MIKROPROPAGIRANOG OCIMUM BASILICUM L. U TANKOM SLOJU: MODELOVANJE, KARAKTERISTIKE KVALITETA I ENERGETSKA EFIKASNOST
Keywords: micropropagation; O. basilicum L.; thin-layer drying; modeling; characteristic; energy consumption